(untitled) (Journal of Accessibility and Design for All, 2021)
According to the World Health Organization, the rights of persons with disabilities (PwD) worldwide are limited by social and physical barriers that prohibit their full participation in society. Built environment barriers can limit accessibility to transportation, goods and services, healthcare, employment, and overall independent movement. The Eastern Province (EP) of the Kingdom of Saudi Arabia (KSA) has about six per cent of its population designated as having some type of physical disability. Previously KSA-instituted rules and standards have not improved accessibility for PwD in the local built environment. This research attempted to determine the extent of accessibility in EP by surveying 183 persons with disabilities to ascertain what elements of the built environment are problematic for them and what they believe requires improvement. According to this survey, PwD felt elements that are essential to accessibility, such as ramps, elevators, restrooms, signage, and egress, are difficult to navigate. Commonly used public locations such as medical centres, restaurants, shopping, mosques, and banks each had obstructive elements that prevented PwD from fully using the spaces. Saudi Arabia is currently in the process of phasing in technical and social programs regarding the built environment that should improve accessibility for PwD, but current conditions are inadequate.